The effects of climate change on rural livelihoods in Indaba ward, Zvishavane - Shoko, Tenson (Midlands State University, 2017)
Extremely high temperatures and very low rainfall has been witnessed in Zimbabwe and this has been the evidence that has shown that climate change is taking place within the country. The Indaba Ward in Zvishavane District has got a population of 5067 people, 2307 men and 2660 women. These changes in climatic conditions have been witnessed specifically in agro-ecological regions 4 and 5 located and these changes have affected the sources of livelihood especially of the rural population who depends mostly on rain for a living. The scope of the study was to unveil a number of issues which are the negative effects of changes in climatic conditions on the Indaba Ward people in Zvishavane District. Low rainfall and high temperatures have affected all sources of livelihood which includes wild fruits, wild animals, agricultural sector, water sources and also livestock. It also brings out the ways or strategies that have been used by the locals in a bid to adapt to the harsh climate conditions. The strategies such as conservation farming, planting of drought resistant crops, the water harvesting strategy, livestock feeding programs and water harvesting among others were implemented by the locals to survive these harsh conditions. The researcher was able to gather this information through the use of interviews and questionnaires. The research also brings out the strategies that can be adopted by the locals to improve their livelihood standards.